UPAYA GURU MEMOTIVASI SISWA PADA PROSES PEMBELJARAN IPS KELAS VIII SMP NEGERI 5 PONTIANAK - Panggabean, Tiurma Yuspin; Aminuyati, Aminuyati; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study is to find out the effect of giving motivation from the teacher in the learning process of social science in class VIII SMP N 5 Pontianak that occur and giving gifts and praise the method in is study is a case study because in this study the author tried to investigate and obtain the facts of the teacher explaining the learning material of social science in clauding not listening to learning material,shy asking questions, busy chatting and even sleeping in class.the rom of motivation given by the teacher only provides additional value in providing motivation to students and infrastructure, social science subject teacher’s explanation, the teacher’s efforts to overcome the contra science teaching hours to several meetings an give a sign in the name also if the teacher conseling guidance and the teacher calls the perents of the studends know the behavior of the child in school because thr teacher and parents colaborationt is very important in shaping the character of studentsKeywords: teacher motivating efforts, teacher motivate, teacher motivation